Performatividad y plástica: el cruzamiento artístico en la obra de Leandro Soto durante la década ‘contaminada’ de los 80s en Cuba - Valencia, Marelys (Latin American Theatre Review, 2016)
This study focuses on the relationship between theatre and visual and performance art in the work of Leandro Soto during the 1980s, when Cuban cultural policy aimed at “ideological purity” and constrained artistic freedom. Ironically, this attitude catalyzed the contamination of disciplines and a spirit of anti-normalization among artists, thus bringing about a dialogue between art, memory, and the historical archive. This article argues that such an integration of artistic codes, along with the recycling of the archive, promoted the role of performance art as a hybrid and contestatory practice par excellence, not only in Havana but in other parts of Cuba as well. Finally, by analyzing the performance piece Ancestros and the play Weekend in Bahia, where Soto returns as set designer, the study emphasizes the potential of art to contest and shape collective memory.